Global, regional, and national incidence and mortality of neonatal sepsis and other neonatal infections, 1990–2019 - Li, Jie; Shen, Lin; Qian, Kun (Frontiers in Public Health, 2023)
Background Neonatal infections, especially neonatal sepsis, are one of the major causes of incidence and mortality in pediatrics. However, the global burden of neonatal sepsis and other neonatal infections (NSNIs) remains unclear. Methods From the 2019 global disease burden study, we collected annual incident cases, deaths, age-standardized incidence rates (ASIRs), and age-standardized deaths rates (ASDRs) of NSNIs in the past 30 years. Analysis indicators included the percentage of relative changes in incident cases and deaths, and the estimated annual percentage changes (EAPCs) of ASIRs and ASDRs. Correlations were assessed between the EAPCs of ASIRs and ASDRs and social evaluation indicators, including sociodemographic index (SDI) and universal health coverage index (UHCI). Results Globally, the number of incident cases of NSNIs grew by 12.79% per year, and the number of deaths dropped by 12.93% per year. During this period, global ASIR of NSNIs increased by 46% annually on average, while ASDR decreased by 53% annually on average. The ASIR and ASDR of female NSNIs were consistently lower than that of male NSNIs. The EAPC of female ASIR was 0.61, nearly twice that of male ASIR, and female ASIR was growing rapidly. The same declining trends of ASDR were noted in males and females. The ASIR of NSNIs in high-SDI regions grew by an average of 14% annually from 1990 to 2019. Except for high-SDI regions, the ASIRs of other 4 SDI regions maintained a rising trend at a high level, and were improved in the past 10 years. The ASDRs of all 5 SDI regions generally showed a downward trend. The region with the highest ASIR of NSNIs was Andean Latin America, and Western Sub-Saharan Africa had the highest mortality. We found a negative correlation between EAPCs of ASDRs and UHCI in 2019. Conclusion The global health situation was still not optimal. The incidence of NSNIs remained high, and continues to rise. The mortality of NSNIs has decreased, especially in the countries/territories with high UHCI. Therefore, it is crucial to improve the overall awareness and management of NSNIs, and take interventions for NSNIs worldwide.